PENGARUH UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kasisariah, Tris Rusilawati; Hayani, Hayani; Amaludin, Amaludin; Pahlan, M. (LP2M Universitas Bina Bangsa, 2025)
This study aims to determine the influence of company size and liquidity on financial performance. This study uses a sample of insurance companies listed on the Indonesian stock exchange. The approach taken in this study is an associative approach and the type of data used is quantitative data in the form of financial statements. The population in this study is insurance companies listed on the Indonesian stock exchange. The sampling technique in this study uses purposive sampling so that 16 insurance companies are obtained as samples. The data analysis techniques in this study used classical assumption tests, including normality tests, multicollinearity tests, heterokedasticity tests, multiple regression analysis, T tests, F tests, and determination coefficient tests with the help of SPSS For windows software version 25. The results of this study show that company size does not have a significant effect on the financial performance of insurance companies listed on the Indonesian stock exchange. Liquidity does not have a significant effect on the financial performance of insurance companies listed on the Indonesia Stock Exchange.Company size and liquidity together do not have a significant effect on the financial performance of insurance companies listed on the Indonesia Stock Exchange